Former foster youths in Andalusian prisons: an approach to self-reported delinquency and involvement with the juvenile justice system. - Rojas Varón, Angie Steffania (My University, 2023)
The general aim of the research project JEPRAN: "Former foster youths in Andalusian prisons" is to identify and understand the situation of young foreigners who have been under the child protection system and are currently in prison. Based on the hypothesis that this is an over-represented group, the approach is carried out through a validated questionnaire distributed to four profiles of young people: foreigners former foster minors, foreigners who arrived in Spain with their families as minors, nationals former foster minors and nationals. The questionnaire allows to explore the life course of these profiles and their relationship with criminal and child protection institutions. It specifically asks for self-reported delinquency both before and after adulthood and identifies cases where youths have been processed through the juvenile justice system for an offence committed between the ages of 14 and less than 18 resulting in a sentencing measure. This research highlights the confluence between the fields of law related to foreigners, child protection and criminal law. In particular, addressing self-reported delinquency and the involvement with the juvenile justice system of young migrants and nationals in prison, allows to identify risk situations and vulnerabilities that should be considered in the design of preventive strategies based on the incidence and prevalence of their delinquency.
Keywords: Delincuencia juvenil - Andalucía; Former foster youths in prison; Delinquency; Juvenile justice